Rayuela de poderes desde la novela El último juego - Mauro, María del Carmen (2016)
Central American literature is marked by a strong influence of it's native History and politics due to events that have guided the development of countries of the isthmus. In this context writers and intellectuals have given their grain of sand to reveal the struggles of the country to wich they belong to. This is the case of the Panamanian Gloria Guardia and her novel The last game, wich without being historic, puts into evidence the problem of the Canal, from the fragmented conciousness of one of her character in wich the public and the private atmosphere mix together, wich leads us to confirm that the oligarch-bourgeois' genealogy, the chronology of the Canal treaties and the U.S. colonialism are one urgent matter to resolve.